Smart phone ophthalmoscopy: a potential replacement for the direct ophthalmoscope. (November 2018) - Mamtora, Sunil; Sandinha, Maria; Ajith, Amritha; Song, Anna; Steel, David
Abstract Purpose The purpose of this study is to evaluate a commercially available smartphone ophthalmoscope, D-EYE, as compared with the direct ophthalmoscope when used by a cohort of final-year medical students in a prospective study. Methods Two-hundred fundal examinations were performed on the eyes of 10 mannequins featuring 5 unique fundal images by 20 final-year medical students from Newcastle University. Each student examined the five fundal images twice, once each with a direct ophthalmoscope and D-EYE in a random order. Students recorded their findings at the optic nerve, macula, and retina in an objective questionnaire, and the findings were analysed by an observer masked to the examination technique. Results Students provided more accurate clinical descriptions of their findings when using D-EYE as opposed to using the direct ophthalmoscope (p  < 0.05). In addition, we found that students were overall more likely to make a correct diagnosis based on their findings when using D- EYE compared with the direct ophthalmoscope. Conclusion Our study suggests that the use of a smartphone-based alternative to the direct ophthalmoscope may improve the accuracy and quality of fundal examinations by non-ophthalmologists.